Effects of adding red wine on the physicochemical properties and sensory characteristics of uncured frankfurter-type sausage. (November 2016) - Feng, Xi; Sebranek, Joseph G.; Lee, Hyun Yong; Ahn, Dong Uk
Abstract: The aim of this work was to evaluate the quality and sensory characteristics of RTE frankfurter-type sausage cured with celery juice powder and including red wine. Four frankfurter treatments including a conventionally cured treatment without red wine (control) and three treatments cured with pre-converted vegetable juice powder and 0%, 5% or 10% ( v / w ) red wine were prepared. Results showed that adding 5% red wine increased the a*-value, and the textural resilience, cohesiveness and springiness of the frankfurters, as well as decreased lipid/protein oxidation of the final products. Added wine also introduced new volatiles (alcohol and ester compounds) to the frankfurters. The principal component (PC) analysis showed that the pre-converted vegetable juice powder achieved the same effects as the conventional curing agents for typical frankfurter properties. However, the addition of excess amounts of red wine (10%) to the meat batter decreased the pH of meat batter and accelerated lipid oxidation. Highlights: The qualities of frankfurters addition of red wine were investigated. Pre-converted vegetable juice powders can replace conventional cured agents. 5% red wine decreased lipid/protein oxidation and introduced new volatiles. Excessive addition of wine (10%) produced negatively effect on frankfurters.